Inside Back Cover: A Gold(I)‐Catalyzed Domino Coupling of Alcohols with Allenes Enables the Synthesis of Highly Substituted Indenes (Chem. Eur. J. 41/2016). Issue 41 (21st September 2016) - Preinfalk, Alexander; Misale, Antonio; Maulide, Nuno
Abstract : The domino coupling of alcohols with allenes is reported. In this transformation, a gold catalyst orchestrates the sequential cyclization and C−C coupling of aromatic allenes and benzylic alcohols to generate indene products in high yields. This reaction cascade proceeds with water as the only by‐product and does not need strict exclusion of moisture or oxygen. More information can be found in the Communication by N. Maulide et al. onpage 14471 ff.